From Past Aspirations to Present Achievements: A Case Study of Three K-8 Schools Successfully Educating Roma Students - Curcic, Svjetlana; Lapat, Goran; Susec, Branko; Ignac, Benjamin (International Journal of Multicultural Education, 2018)
This case study focuses on education in three K-8 schools in Medjimurje County, Croatia. The object of inquiry is the development of successful educational practices for Roma students. Until recently, only a limited number of Roma students completed basic K-4 schooling. Today all students at these three schools complete K-8 education, with some Roma students going on to pursue secondary and tertiary education. We examine some of the processes that took place in creating the change, along with the principals’, teachers’, and Roma assistants’ views and actions.